Handbook of research on multimedia cyber security - Gupta, Brij 1982-; Gupta, Deepak 1983- (IGI Global, 2020)
"This book explores recent and future advancements in multimedia security and processing. It also presents new and recent algorithms in various emerging areas for copyright protection, content authentication, ownership authentication, and identity theft"--
Description based on title screen (IGI Global, viewed 04/15/2020)
Keywords: Biometric identification; Database security; Multimedia communications / Security measures